Pasmodium Vivax Malaria Complicated by Neurological, Jaundice and Haemophagocytic Syndrome - Ram Kumar, TV; Baghmar, S (Journal of Nepal Paediatric Society, 2010)
We are describing a case of plasmodium vivax malaria in a child with complications including pancytopenia secondary to marrow involvement, jaundice and neurological features. The child improved with antimalarial treatment. DOI: 10.3126/jnps.v30i3.3922 J Nep Paedtr Soc 2010;30(3):168-170